Estudo petrográfico e geoquímico dos ironstones da base da Formação Pimenteiras, Borda Oeste da Bacia do Parnaíba, Tocantins - AMARO, Gabriel de Jesus Lavareda (2015)
Ironstones that occur at the base of the Devonian Pimenteiras Formation (northwestern border of the Parnaíba basin) were investigated along the Xambioá-Vanderlândia and Colinas do Tocantins-Couto Magalhães sections. The ironstones consist of discontinuous decimeter-thick layers intercalated in sandstones and shales that underlie rocks of the Neoproterozoic Araguaia belt. The Xambioá-Vanderlândia ironstones are texturally and chemically quite distinct from those of the Colinas do Tocantins-Couto Magalhães area. Besides the presence of oolites, the former shows smaller amounts of terrigenous material (especially quartz) and higher iron oxide-hydroxides proportions. They also are more enriched in V, Sr, Zr and ΣREE, and poorer in Al2O3 and Rb. The North American Shale Composite (NASC) normalized REE distribution pattern is also different, especially concerning the IREEN values, which, being higher in the oolithic ironstones, display convex curves and, being lower in the non-oolithic ironstones, display concave ones. In the field, spatial relationships could not be defined between both ironstone types. It is then suggested that they represent different lithological facies of the same iron formation. Probably, the deposition of the non-oolithic facies occurred in deeper and quieter waters away from the continental border, where larger amounts of detrital sediments were discharged, whereas the deposition of the oolithic facies took place in shallower and more agitated waters, with less supply of terrigenous material. Iron was largely derived from the erosion of continental areas where reduced environments favored its mobilization and transport by rivers as suspended particles, colloids, and organic complexes.